Krest'janstvo i sel'skoe chozjajstvo Sibiri v 1917-1961 gg. [Pod red. V.S. Flerova, L.M. Gorjuškina, N.Ja. Kuščina, i dr. Pri učast. L.M. Gorjuškina, V.T. Agalakova, M.M. Vyborova i dr.] ("Nauka", 1965)
An SSSR, Sibirskoe Otdelenie.